Johnius taiwanensis, a new species of Sciaenidae from the Taiwan Strait, with a key to Johnius species from Chinese waters - Chao, Ning Labbish; Chang, Chih-Wei; Chen, Meng-Hsien; Guo, Chang-Chang; Lin, Bai-An; Liou, You-Yu; Shen, Kang-Ning; Liu, Min (Zootaxa, 2019)
A new sciaenid fish, Johnius taiwanensis, is described from the southeast coast of mainland China from Zhejiang to Guangdong, Hong Kong, and west coast of Taiwan. Johnius taiwanensis sp. nov. can be distinguished from other Johnius species by having a grayish dorsal half of body divided by a clear line from a whitish ventral half, and a black spot at the dorsal half of pectoral-fin axil, appearing as a distinct dot at the most dorsal point of the pectoral-fin base. First dorsal fin black tipped, other fins pale to dusky but never darkly pigmented. The species lacks distinctly enlarged teeth on upper and lower jaws. Body scales ctenoid, moderately large, with five or six rows between first dorsal-fin origin and lateral line. It is one of the most abundant sciaenids found in the shallow coastal waters (<20 m) of southeast mainland China and the west coast of Taiwan. It has often been misidentified as J. macrorhynus in the region. Phylogenetic analysis from all 27 sciaenid species found in Chinese waters based on the complete COI and 16S rRNA gene sequences confirmed that the genus Johnius is monophyletic and J. taiwanensis is placed as a sister species of J. trewavasae. Acoustic analysis has shown that J. taiwanensis produces a unique sound among fishes in Taiwan coastal waters.